Fractais: uma abordagem introdutória - Farias, Mailson Alves (2019)
In this work, we study Fractal Geometry, characterizing some classic fractals and presenting some historical aspects related to this theory. Furthermore, we want to highlight that Fractal Geometry allows us to observe an interesting connection among the construction of mathematical elements and some objects present in the nature. An interesting aspect is that some related concepts can be approached in elementary and high school